Toxicological analysis and anti-inflammatory and antioxidant evaluations of extract, fractions and secoxyloganin obtained from Guettarda viburnoides Cham. & Schltdl. in mice - de Oliveira Junior, Pedro Cruz; Sanjinez Argandoña, Eliana Janet; dos Santos, Sidney Mariano; Santos, Jéssica Maurino dos; de Souza, Maiara Fava; Faoro, Janaine Alberto Marangoni; Kassuya, Cândida Aparecida leite; Arena, Arielle Cristina [UNESP]; Matos Manoel, Beatriz de [UNESP]; Silva, Rosilda Mara Mussury Franco; Formagio, Anelise Samara Nazari (Elsevier, 2025)
Ethnopharmacological relevance: Guettarda viburnoides, “veludinho do campo, is traditionally used for the treatment of pain and inflammatory conditions in humans; however, only one scientific study has reported this effect in an ear inflammatory model. Therefore, it is necessary to explore other in vivo models and the chemical composition of this medicinal plant. Aim of the study: A chemical investigation of methanolic extract of G. viburnoides (MEGV) (leaves) led to the isolation of secoxyloganin (GV-1). In addition, the preclinical safety of MEGV (in acute and subacute toxicological models, gavage = p.o.), antioxidants of MEGV, ethyl acetate (EAFGV) and hydromethanolic (HMFGV) fractions were tested using free radical scavenging and lipid peroxidation methodologies, and the anti-inflammatory effects of MEGV, HMFGV and GV-1 (p.o.) were evaluated on carrageenan and complete Freund's adjuvant (CFA) models of inflammation in mice. Materials and methods: MEGV was obtained from air-dried leaves by maceration with methanol at room temperature. MEGV was then purified by liquid-liquid partitioning, to obtain the EAFGV and HMFGV fractions. Purification of HMFGV afforded GV-1. The quantification of total phenols, flavonoids, flavonols, and condensed tannins was subsequently performed for MEGV. The antioxidant activity of 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2, 2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and oxidation of β-carotene were evaluated in MEGV and its fractions. The anti-inflammatory activity of MEGV (3, 30, and 100 mg/kg, p.o.) was assayed in carrageenan-induced models, followed by assessments of MEGV (100 mg/kg, p.o.), HMFGV (3 and 30 mg/kg, p.o.) and GV-1 (3 mg/kg, p.o.) in CFA-induced models in mice (including paw oedema, mechanical allodynia and cold sensitivity). Acute (14 days of MEGV, 2000 mg/kg, p.o.) and subacute (28 days, MEGV 30, 100, and 300 mg/kg, p.o.) toxicity was assessed in female Swiss mice. Results: The major compound was secoxyloganin (GV-1). The oral acute toxicity test of MEGV revealed no evidence of toxicity, indicating low toxicity according to the Organization for Economic Cooperation and Development (OECD) guidelines. In the subacute toxicity group, no clinical signs of toxicity or changes in body weight, water consumption, food consumption, or organ weight or morphology were observed after 28 days of gavage with MEGV (30, 100, and 300 mg/kg) compared with those in the control group. MEGV, EAFGV, and HMFGV showed significant free-radical scavenging and lipid peroxidation activities, with IC50 values ≤ 26.38 ± 4.56 μg/mL. In in vivo anti-inflammatory assays, MEGV (3, 30 and 100 mg/kg) reduced carrageenan-induced oedema (2 and 4 h) and hyperalgesia (3 and 4 h). In the CFA model, MEGV (100 mg/kg), HMFGV (30 mg/kg) and GV-1 (3 mg/kg) reduced inflammation (at 3, 4 and 24 h) in all parameters (oedema, mechanical allodynia and cold sensitivity). Conclusion: This study revealed that G. viburnoides has antioxidant and anti-inflammatory properties, and no toxicity was detected after acute or subacute gavage with MEGV, validating its traditional use in the treatment of inflammatory conditions.
Keywords: Analgesic; Carrageenan; Complete Freund's adjuvant; Oedema; Secoiridoid; Veludinho